Microsoft Word Training To Improve The Digital Competence Of Students At MTs Miftahul Arifin Bangsring - Zaehol Fatah; Ahmad Yasin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Students need to have good digital skills because of the growth of digital technology. This is particularly important for using office applications like Microsoft Word. However, from what we saw at MTs Miftahul Arifin Bangsring, many students still had trouble using basic features of Microsoft Word, such as formatting text, creating tables and saving documents. This community service activity was focused on helping students become better at using digital tools by providing training in Microsoft Word. The ways we did this included talking with others, watching what happens, practicing directly, and checking how things went. The event took place on February 15, 2026, and included 8 members from the OSIM management team. The results indicated that the training helped students get better at using Microsoft Word. From the satisfaction survey results, many participants strongly felt that the training was easy to follow and helpful for supporting digital learning activities in school.